The Effect of Liquidity, Activity and Solvability on Profitability - Afin, Erika Fahma; Sofyaun, Ashari; Matyani, Matyani (Riwayat: Educational Journal of History and Humanities, 2025)
Objective study This is for know influence Liquidity, Activity and Solvency to Profitability in Sub - sector Companies transportation listed on the Indonesia Stock Exchange. In the study This amount population as many as 37 companies and samples as many as 27 companies were taken with use the specified criteria author. The method used in study This is analysis regression multiple with secondary data taken from report annual company during period 2021 to 2024. Research results show that in a way partial Current Ratio and Total Asset Turnover variables have direction connection positive and influential significant to profitability, while the Debt to Asset Ratio does not influential significant to profitability